2018
DOI: 10.1128/mra.00929-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Acinetobacter radioresistens Strain LH6, a Multidrug-Resistant Bacteriophage-Propagating Strain

Abstract: Antimicrobial resistance is a major problem worldwide. Understanding the interplay between drug-resistant pathogens, such as Acinetobacter baumannii and related species, potentially acting as environmental reservoirs is critical for preventing the spread of resistance determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…We previously sequenced strain A. radioresistens LH6 described in this study. LH6 lacks plasmids, but encodes several putative MBLs, which can account for its resistance profile ( Crippen et al, 2018 ). Interestingly, LH6 also encodes bla OXA–2 3 with 100% amino acid homology to the A. baumannii ASM74664v1 homolog, but no broad carbapenem, cephalosporin or β-lactamase resistance phenotype was observed ( Table 1 and Supplementary Figure S4 ), which is normally associated with the presence of this gene ( Pfeifer et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously sequenced strain A. radioresistens LH6 described in this study. LH6 lacks plasmids, but encodes several putative MBLs, which can account for its resistance profile ( Crippen et al, 2018 ). Interestingly, LH6 also encodes bla OXA–2 3 with 100% amino acid homology to the A. baumannii ASM74664v1 homolog, but no broad carbapenem, cephalosporin or β-lactamase resistance phenotype was observed ( Table 1 and Supplementary Figure S4 ), which is normally associated with the presence of this gene ( Pfeifer et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 5/7 of the isolated phages were segmented RNA phages that are known to undergo recombination at high rates ( Simon-Loriere and Holmes, 2011 ). In addition, genomic sequencing of A. radioresistens LH6 ( Crippen et al, 2018 ) identified two possible chromosomal prophages, including one Mu-like, that may also be involved in AMR gene transduction ( Braid et al, 2004 ). One of these prophages was indeed isolated after induction with mitomycin C and is being described in a separate manuscript (Crippen et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…For the identification of the induced prophage SLAP1, primers were designed that target the capsid genes of prophage 1 and prophage 2 [ 6 ]. Prophage 1 was detected with the primers pP1capsid-F and pP1capsid-R, prophage 2 was detected with the primers pP2capsid-F and pP2capsid-R (primers listed in Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the majority of phage screens have been directed toward this pathogen, and the host range for these Acinetobacter -infecting phages will be limited to A. baumannii . Recently, we isolated the Acinetobacter radioresistens strain LH6 from chicken feces on a free-range farm [ 6 ]. We found that this multidrug resistant reservoir strain encodes genes associated with resistance to toxic metals and quaternary ammonium compounds [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation